ISLAMIC RELIGIOUS EDUCATION TEACHERS' STRATEGIES TOWARDS INSTILLING MULTICULTURAL VALUES OF JUNIOR HIGH SCHOOL STUDENTS 3 PALOPO - Muthia Muthmainnah; Muh. Abdi Imam; Muzakkir; Rusdi T (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study addresses the need to nurture multicultural values in increasingly diverse school environments. At SMP Negeri 3 Palopo, where students represent varied ethnic, religious, and cultural backgrounds, Islamic Religious Education (PAI) teachers are central in fostering tolerance, empathy, and mutual respect. The research aims to explore and interpret the teachers' strategies to embed multicultural values and reveal the meanings attached to their practices. Using a qualitative phenomenological approach, participants—comprising PAI teachers, students, and school leaders—were selected purposively. Data were collected through in-depth interviews, participant observation, and document review, and then analyzed thematically with triangulation and member checking to ensure validity. Findings identify three interrelated strategies: integrating multicultural values into lesson content, applying interactive and participatory teaching methods, and consistently modeling inclusive behaviors in daily school life. These strategies mutually reinforce one another, shaping students’ knowledge, attitudes, and social skills and transforming multicultural principles into real-life practices. The study concludes that effective multicultural education blends curriculum integration, active pedagogy, and exemplary conduct. Theoretically, it extends culturally responsive teaching to religious education; practically, it offers actionable guidance for schools aiming to build inclusive, harmonious learning spaces.